SCIENTIFIC APPROACH-INTEGRATED VIRTUAL SIMULATION: A PHYSICS LEARNING DESIGN TO ENHANCE STUDENT’S SCIENCE PROCESS SKILLS (SPS) - Siswanto, Siswanto; Gumilar, Surya; Yusiran, Yusiran; Trisnowati, Eli (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2018)
Physics learning using scientific approach-integrated the real laboratory is a process to train student’s science process skills in the classroom. However, it is little known that using scientific approach-integrated virtual simulation has huge potential in training student’s science process skills. This study carried out was to acquire the description of enhancing student’s science process skills in physics learning that its learning activities refer to the syntax of scientific learning activities. The activities of learning were conducted with integrating virtual simulations during two times face to face in the classroom activities. There were 31 students as participants in one public senior high school in Bima, Indonesia. The pre-experiment method with one group pretest-posttest design is shown to illustrate the intervention of training of science process skills involved in the classroom. The data sources for this study were the result of the student’s score about science process skills measured by essay test combined rubrics.Furthermore, the science process skills measured from students encompassed skills of observing, communicating, clarifying, measuring, predicting, and interpreting. The results of the study depicted that there was significant increase of student’s science process skills (<g>=0.34; intermediate level) and significant difference between pretest score and posttest score (z=-4.861; p=0.0001).